(untitled) (Journal of Environmental Science and Natural Resources, 2016)
A total of 18 non-canned soft drinks and 12 canned soft drinks of different brands were collected from markets in Chittagong City of Bangladesh. It was found that, lead concentrations were significantly low in non-canned soft drinks. The highest level of lead content was obtained 0.016 mgL-l. The content of lead in non-canned soft drinks was found in the range from 0.005 mgL-l to 0.016 mgL-l. Lead concentrations in non-canned soft drinks were found below the maximum allowed limit for lead. Among all non-canned soft drinks, chromium was present in 11 samples. The highest concentration of chromium was found 0.018 mgL-l. The concentrations of chromium in non-canned soft drinks were in the range from 0.006 mgL-l to 0.018 mgL-l. Lead was found in 7 canned soft drinks. The lead concentration was in the interval from 0.006 mgL-l to 0.017 mgL-l. The highest level of lead was found 0.017 mgL-l. Chromium was found in 8 canned soft drinks. Concentration of chromium was in the range from 0.007 mgL-l to 0.019 mgL-l in canned soft drinks. The maximum concentration of chromium was found 0.019 mgL-l in canned soft drinks. J. Environ. Sci. & Natural Resources, 8(2): 153-156 2015